PENAKSIR DUAL RASIO-CUM-PRODUK UNTUK RATA-RATA POPULASI DENGAN MENGGUNAKAN KOEFISIEN KORELASI - Ronni Vel Ilham; Rustam Efendi; Haposan Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses three ratio-cum-product estimators for the population mean usingthe coefficient of correlation on simple random sampling i.e. ratio-cum-productestimator, dual ratio-cum-product estimator, and combination dual ratio-cum-productestimator. The three estimators are biased estimators. Then the mean square errors aredetermined. Furthermore, these mean square errors are compared to the mean squareerror of each estimator. This comparison shows that the combination dual ratio-cum-product estimator using coefficient of correlation is more efficient than other estimators.